Synthesis of indolo-quinonediimine derivatives by the thermolysis of 5-(1-benzotriazolyl)-substituted spiro[2H-benzimidazole-2,1‘-cyclohexane] - Le, Huu Phuoc; Kelbig, Anna; Lindauer, Andreas; Neidlein, Richard; Suschitzky, Hans (Journal of chemical research online. Synopses, 2004)
Nucleophilic introduction of the 1H-benzotriazole ring into spiro[2H-benzimidazole-2,1‘-cyclohexane] and spiro[2H-imidazo[4,5-b]pyridine-2,1‘-cyclohexane], followed by Graebe-Ullmann thermolysis, and also the reduction and formic acid cyclization of five spiro[cyclohexane-1,2‘-2‘H-imidazo[4,5-b]pyridine] derivatives to give 5-substituted 1H-imidazo[4‘,5‘:5,6]pyrido[1,2-a]benzimidazoles, are described.